2019
DOI: 10.21109/kesmas.v14i1.2257
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Self-Regulated Learning for Improving Dietary Management and Quality of Life in Patients with Type-2 Diabetes Mellitus at Dr. Ramelan Naval Hospital, Surabaya, Indonesia

Abstract: Self-regulated learning is a process of learning how to manage and regulate oneself to obtain skills and knowledge without depending on others. It is expected that diabetes patients can manage their diabetes by themselves. This study aimed to analyze the effect of self-regulated learning-based educational intervention on quality of life for patients with type-2 diabetes mellitus (DM) at Dr. Ramelan Naval Hospital, Surabaya. This was a quasi-experimental study in the form of pretest and posttest with a control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…It includes autonomic and neurohormonal dysregulation, weight gain, inflammation, and hippocampal structural changes. Two recent meta-analyses of trials of randomized controlled depression treatment in patients with type 2 DM concluded that psychotherapy and antidepressant drugs, respectively, are quite effective for depression and cognitive behavioral therapy (CBT) has a beneficial effect on glycemic control [4], [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…It includes autonomic and neurohormonal dysregulation, weight gain, inflammation, and hippocampal structural changes. Two recent meta-analyses of trials of randomized controlled depression treatment in patients with type 2 DM concluded that psychotherapy and antidepressant drugs, respectively, are quite effective for depression and cognitive behavioral therapy (CBT) has a beneficial effect on glycemic control [4], [5], [6].…”
Section: Introductionmentioning
confidence: 99%